Interações entre vegetação e as áreas centrais de Aracaju/SE e Maceió/AL : índice socioecológico e paisagístico urbano - Kohler, Raquel (2018)
From the discussion of the society-nature theme, the aspects related to the complex relationship between vegetation and urban landscape are discussed. It is understood that the function of vegetation in this context extrapolates aesthetics, since it can constitute a functional infrastructure and positively influence the environmental, social and economic quality. The bibliographic review shows that urban indicators and indices as a subsidy for public policies and for planning are widely used, noticing however, a weakness regarding to indicators and indices related to urban vegetation. From this consideration, the purpose of the thesis was to develop a vegetation analysis instrument in the urban landscape to provide for decision makers a support for planning and management, based on the ecosystem view of the city. The methodology consists on a set of ten indicators that pondered results in the Socioecological and Urban Landscape Index. The proposed indicators are based on the measurement of urban vegetation from spatial categories determined by their specific functions, relating them to the degrees of landscape artificialization, to the diversity of species and to the spatial distribution of the resident population. The vector spatial data and the alphanumeric database of the IBGE Statistical Grid, the geoprocessing and remote sensing techniques, as well as the chosen software show themselves effective for the research purpose. Based on the analysis of data collected from public agencies, field works and interpretation of satellite images, the proposed methodology was tested in spatial clippings corresponding to Aracaju / SE and Maceió / AL central areas, making it possible to compare data, as well as adjustments in methodology. The indicators and index results, the spatial cut-offs analyzed were below to the level considered suitable, and the imbalances found refer especially to the high landscape artificiality and the soil waterproofing, the low amount of vegetation in some spatial categories. It also highlights the lack of attention to local specificities in relation to natural ecosystems, the fragmentation, distribution and unbalanced diversity of vegetation. The survey results also pointed out that the indicators and the socioecological and urban landscape index proposed are appropriated and that the methodology can be applied in different scales and urban contexts. In spite of its importance for future analysis trends, the proposal shows itself as a system that can be fed back to the systemic evaluation of urban green planning and management practices.________________________________________________________________________________________________________________________________